Exercise-induced gastrointestinal injury in endurance athletes: mechanisms, risk factors and clinical implications – a review - Purpura, Aleksandra; Rolski, Wiktor; Przybylska, Zuzanna; Michalska, Paulina; Przystaś, Bartłomiej; Grzechowiak, Magdalena; Podeszwa, Sebastian; Hobot, Mikołaj; Dobosz, Gabriela (Quality in Sport, 2026)
Background. Gastrointestinal (GI) disturbances are commonly reported among endurance athletes and significantly affect performance and health. Prolonged, high-intensity exercise leads to physiological stress responses impairing GI function. Mechanisms such as splanchnic hypoperfusion, increased intestinal permeability, heat stress, and dehydration contribute to exercise-induced gastrointestinal syndrome. Aim. This review summarizes knowledge on exercise-induced GI injury in endurance athletes, focusing on epidemiology, pathophysiological mechanisms, risk factors, clinical manifestations, and management strategies. Material and methods. A literature search was conducted in PubMed, Scopus, Web of Science, and Google Scholar for studies up to 2025. Keywords related to GI symptoms, endurance exercise, intestinal permeability, and splanchnic hypoperfusion were used. Original research articles, systematic reviews, and meta-analyses were included. Results. GI symptoms like nausea, diarrhea, and bloating affect 30% to 90% of athletes depending on conditions. Mechanisms involve reduced splanchnic blood flow, epithelial injury, increased permeability, endotoxin translocation, systemic inflammation, and microbiota alterations. Risk factors include exercise duration, heat stress, dehydration, nutrition, and NSAID use. Severe complications like GI bleeding or ischemic colitis occur in rare cases. Conclusions. Exercise-induced GI injury is a multifactorial condition resulting from physiological, environmental, and nutritional stressors. Understanding these mechanisms and risk factors is essential for effective prevention and management strategies to protect GI health and optimize performance.